Isolation of thermophilic proteolytic microorganism from Lojing Hot Spring, Kelantan. - Noor Azlina Ibrahim (Universiti Malaysia Kelantan, 2010)
Water sampling have been done at four location of the Lojing Hot Spring and each location have different water temperature (70, 60, 50 and 40˚C ). Only samples of 50˚C and 40˚C were showed growth in nutrient broth. Each inoculums have been screened on skim milk agar and two isolates (50a and 50b) of 50˚C samples formed clearing zones around the colonies on the plates. From their protease assay, both isolates have identified as a serine protease producer and from the 16S rDNA identification, isolate 50a closely related to Bacillus subtilis while isolate 50b was closely related to Bacillus licheniformis. These isolates will be used for further studies into the cloning and expression of protease gene.